Portable bedside microcomputer system for management of parenteral nutrition in all age groups. Issue 5 (May 1985) - Ball, P A; Candy, D C; Puntis, J W; McNeish, A S
Abstract : A microcomputer program has been designed to provide comprehensive assistance to the clinician in prescribing parenteral nutrition in children of all ages. It is implemented on a fully portable, independent machine that can be taken to the bedside anywhere in the hospital. The user is guided through a standardised prescribing process based on a well tried protocol and taking into account the patient's age, clinical condition, concurrent parenteral infusions, laboratory findings, and enteral intake. A printout is produced for insertion into the patient's clinical record, giving all concerned in the care of the child a clear, legible record of when, how, and by whom the prescription was calculated. The user can review and amend the proposed prescription before printing, giving ultimate control to the prescriber, not the computer. The system saves time by performing accurately the necessary calculations, and provides financial savings by reducing wastage of parenteral nutrition during the re-introduction of enteral feeding.